SOME DEVELOPMENT RESEARCH TECHNOLOGIES OF DRY EXTRACT TABLETS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The development of new medicines is one of the main problems of modern medicine. In this regard, the development of complex drugs is of particular interest. Their use makes it possible to expand the range of pharmacotherapeutic action, strengthen certain aspects of the therapeutic effect, and reduce undesirable toxic manifestations. This report presents the results of a study on the development of dry extract tablet technology. Theinfluence of the tableting process on the quality of recommended tablets is studied. The technological properties of the obtained tablet masses and the finished product are studied.
Keywords: Dry extract, direct pressing, wet pressing, quality, technological properties.